Perbedaan Hasil Belajar Siswa Kelas X Di SMA Negeri 1 Marawola Melalui Penerapan Model Pembelajaran Kooperatif Tipe Buzz Group Dan Konvensional Pada Materi Sistem Periodik Unsur - Utarid, Sri; Sakung, Jamaluddin; Ratman, Ratman (Universitas Tadulako, 2015)
Many efforts have been done in order to increase the quality of education. One of them is to improve the instructional process. The purpose of this research was to find out the difference of the grade X student’s learning outcomes at SMA Negeri 1 Marawola through the application of cooperative learning of buzz group type and conventional one on the topic of periodic table. The population was the grade X students in the academic year of 2013/2014. The samples were 25 grade XB students as the experimental group (buzz group typpe instruction) and 25 grade XA students as the control group (conventional instruction). The data were collected by using the test on the element periodic system. The testing of the research data was carried out by the t-test statictic analysis of two parts with prerequisite testing: normality and homogenity. It was obtained that the average scores of the experimental group and the control group that is 76.2 and 73.4. Based on the hypothesis analysis with to use statistic t-test it was obtained that tcalculated = 2.89 and ttable = 2.02 on the α = 0.05. this means that H1 was accepted and H0 was rejected, for the the tcalculated was in the H0 rejection. This indicates that there is a difference of the student’s learning outcomes instructed by the cooperative learning of buzz group type and the conventional one at SMA Negeri 1 Marawola.